-3(-8v+1)-5v=3(v-1)-2

Simple and best practice solution for -3(-8v+1)-5v=3(v-1)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-8v+1)-5v=3(v-1)-2 equation:



-3(-8v+1)-5v=3(v-1)-2
We move all terms to the left:
-3(-8v+1)-5v-(3(v-1)-2)=0
We add all the numbers together, and all the variables
-5v-3(-8v+1)-(3(v-1)-2)=0
We multiply parentheses
-5v+24v-(3(v-1)-2)-3=0
We calculate terms in parentheses: -(3(v-1)-2), so:
3(v-1)-2
We multiply parentheses
3v-3-2
We add all the numbers together, and all the variables
3v-5
Back to the equation:
-(3v-5)
We add all the numbers together, and all the variables
19v-(3v-5)-3=0
We get rid of parentheses
19v-3v+5-3=0
We add all the numbers together, and all the variables
16v+2=0
We move all terms containing v to the left, all other terms to the right
16v=-2
v=-2/16
v=-1/8

See similar equations:

| 2=-4w+2(w+3) | | 5x+7=16+2x | | 12y-39=y-(-86) | | -4+5x=96 | | 8n-10=8 | | 8n-2=4 | | 18+3a/7=21 | | (x+1)(2x-50²)=(x-1)(2x+3) | | (x+1)(2x-50)=(x-1)(2x+3) | | (x+1)(2x-5)=(x-1)(2x+3) | | 40=3.14d | | 6a+6=–18 | | 5x-4=-1-2x | | x²-14x+49+36=x²-6x+9+16 | | (x+59)+x=759 | | 7(5x+5)=10(3x+5) | | (x-54)+x=696 | | 5x-7/6=3x-5/4 | | x-54x=696 | | 12x-60+3x-3=6x-18+8x-32 | | 6x-9=3x+5 | | (2x-3)+(6x-5)=3x+12 | | X+123=2y | | 3*7/4x=192 | | -3x^2-150x-20000=0 | | -3x^2-150x+20000=0 | | 4x^2-15x-9=0 | | 3x^2-150x+20000=0 | | 3*4/7x=192 | | 5y-8(5y+2)=-(25y+46) | | X2-3=11÷x | | 4a-1=2a+7 |

Equations solver categories